Tindak Pidana Terkait Akses Akun Mobile Banking dengan Mengaktifkan Kembali Simcard yang Sudah Tidak Aktif - Rengga Aditya Mulawardhana; Go Lisanawati (Fakultas Hukum Universitas Surabaya, 2020)
Criminal activities related to the use of the internet (cyber crime) are growing rapidly in Indonesia with various modes. This article aims to analyze one of the cases that has occurred regarding illegal access to fund transfers based on normative juridical methods. The action being studied was access to a mobile bank account using an inactive card to transfer funds. Based on this mode, two violations occurred in 2 (two) laws as well as Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 3 of 2011 concerning Fund Transfers. The result of this research is that perpetrators with mobile banking account access mode by using an inactive card and transferring funds can fulfill the criminal elements according to the provisions of Article 30 paragraph (3) of Law Number 11 of 2008 concerning Electronic Information and Transactions, and can subject to criminal penalties according to Article 46 paragraph (3) of Law Number 11 of 2008 concerning Electronic Information and Transactions, and also fulfills criminal elements according to the criminal provisions of Article 81 of Law Number 3 of 2011 concerning Fund Transfers.